Perlindungan Hak Asasi Manusia Terhadap Perempuan Korban Kekerasan Seksual - Kurniawan, Nizar Agung (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
Human rights and sexual violence are major issues in Indonesia, as the former violates victims' human rights and dignity. Situations are made worse by stigma and a lack of security. In addition to examining potential alternatives for creating a future free from sexual violence, this essay looks at Indonesia's link between sexual violence and human rights. The realization of victims' rights is hampered by stigma and a lack of access to rehabilitation services. Human Rights (HAM) are fundamental rights that all people naturally possess since they are gifts from God that are ingrained in all people and need to be protected, loved, and cherished. Human rights ought to be protected by the relevant constitution of Indonesia, a constitutional state of law. Due to the high annual incidence rate, sexual violence is still a significant problem in Indonesia. One way that human rights are violated is through sexual violence. This study aims to examine sexual violence, which is regarded as a human rights violation. Article 28 of Chapter XA of the Indonesian Constitution contains regulations pertaining to the right to be free from discriminatory treatment and treatment. A child's right to life, development, and protection from discrimination and violence are all governed by laws. Due to its connection to human dignity, sexual assault must be viewed through the lens of crimes against human rights